Sensitivity assessment and simulation of water resource security in karst areas within the context of hydroclimate change. (10th June 2020) - Yin, Boling; Guan, Dongjie; Zhou, Lilei; Zhou, Jian; He, Xiujuan
Abstract: Water security plays an important role in human sustainable development since the 21st century. This paper focuses on the water resource security in the karst areas of Guizhou province, China, to elucidate the stress mechanism and feedback relationship affecting water resource security sensitivity. Firstly, an assessment indicator system for water resource security is constructed with regard to the characteristics of water resources in the karst area. Secondly, according to the fuzzy mathematics theory, an assessment model for water resource security is constructed to dynamically evaluate water resource security in the karst area over a given time scale. Finally, to analyze the sensitivity and the stress mechanism of regional water resource security in the context of hydroclimate change, this paper establishes a system dynamics model, and sets four scenarios, namely, high flow year, normal flow year, partial dry year and dry year, to simulate and figure out the optimal scenario of regional water resource security. The results demonstrate that the integrated security of water resources in the karst area is highly sensitive in the context of hydroclimate change. In addition, the sensitivity of water resource security in the karst area would decrease from high flow year to dry year in the future. Highlights: Fuzzy mathematical and SD are used to measure water resource security. From 2001 to 2015, water resource security eigenvalue increased from 2.03 to 4.65. Water subsystems have diverse security sensitivity under hydroclimate change. Water resource security sensitivity varies from dry year to high flow year.